Retracted: CDP/Cut is an osteoblastic coactivator of the Vitamin D Receptor (VDR). (15th January 2013) - Ochiai, Eiji; Kitagawa, Hirochika; Takada, Ichiro; Fujiyama, Sally; Sawatsubashi, Shun; Kim, Mi‐sun; Mezaki, Yoshihiro; Tsushima, Yu; Takagi, Ken‐ichiro; Azuma, Yoshiaki; Takeyama, Ken‐ichi; Yamaoka, Kazuyoshi; et al.
Abstract: Retraction: The following article from the Journal of Bone and Mineral Research, "CDP/Cut Is an Osteoblastic Coactivator of the Vitamin D Receptor (VDR)" by Eiji Ochiai, Hirochika Kitagawa, Ichiro Takada, Sally Fujiyama, Shun Sawatsubashi, Mi‐sun Kim, Yoshihiro Mezaki, Yu Tsushima, Ken‐ichiro Takagi, Yoshiaki Azuma, Ken‐ichi Takeyama, Kazuyoshi Yamaoka, Shigeaki Kato, Takashi Kamimura, published online on December 11, 2009 in Wiley Online Library (wileyonlinelibrary.com), has been retracted by agreement between the authors, the journal Editor in Chief, Thomas Clemens, the American Society for Bone and Mineral Research and Wiley Periodicals, Inc. The authors have requested the retraction based on their acknowledgement that several of the figures did not reflect the observations presented.